Vegetarian Diets and Their Multciple Identities - Ferreira, Ana Cristina; Rezende, Daniel Carvalho de (Revista de Negócios, 2023)
The objective of this work is to identify the identity aspects of semivegetarian, vegetarian and vegan consumers and to understand how each group perceives one another. The study has a qualitative and descriptive approach. Data collection took place through semi-structured interviews with 42 consumers adept at vegetarian diets. Data were analyzed using Content Analysis, with mixed grid and use of Nvivo Software. The results show that vegetarian identities are multiple and multidisciplinary. There is an expectation when a person declares himself semi-vegetarian, vegetarian or vegan. Thus, identity coherence in their actions is expected. In the virtuous process, the individual understands the position he is currently in and the evolutionary steps he can follow. However, there are also conflicts between the studied groups and within the defined groups themselves. This advanced study in understanding the construction of the identity of semi-vegetarians, vegetarians and vegans, makes it possible to understand the vision that brings them closer to the identities of themselves, and that of others. Therefore, there are differences in perception between semivegetarians, vegetarians and vegans, and these differences in identity are reflected in aspects related to personal life, considering conflicts and the virtuous process.